Penafsiran Kontekstual Ayat Al-Qur’an Tentang Relasi Laki-Laki dan Perempuan - Adrika Fithrotul Aini (LPPM Institut Pesantren KH. Abdul Chalim, 2021)
This paper examines the reinterpretation of the relation verses between men and women. There are still many commentators who perpetuate interpretations that discriminate against one of them. Some things that will be answered in this paper are those related to verses in the domestic and public sphere. The method used is the contextual interpretation method based on the application of Abdullah Saeed's theory regarding the search for a hierarchy of values ​​to be applied in any time and place. This paper produces new meanings to the verse on relations, including the creation of equal autonomy rights between husband and wife in the context of self-actualization to create a harmonious family without mutual discrimination by prioritizing the elements of justice, compassion and cooperation. Meanwhile, authentic meaning in the public sphere is a sign of women's activeness in affirmative politics for self-actualization as humans who have the same ability to become leaders. Everything is based on a sense of respect and freedom for all regardless of gender.